(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Students are required to acquire certain knowledge, skills and competencies, as well as support them in various life situations. This goal can be achieved through integrated software applications, lessons, and extracurricular activities.